The role of Islamic crowdfunding and the mediating effect of technology adoption on SME’s sustainability / Norasekin Ab Rashid, Norhasdalina Hasim and Maziana Zainal Abidin - Ab Rashid, Norasekin; Hasim, Norhasdalina; Zainal Abidin, Maziana (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
Small and Medium Enterprises (SMEs) contribute to many factors in generating the economy such as income and employment generation and distribution of product and services in the city and rural areas. Almost 98.5 percent of business establishments in Malaysia are SME companies cut across all sizes and sectors. However, SMEs in Malaysia are unable to access external financing due to excessive rigid procedures imposed by financial institutions and government agencies. To address and resolve this critical issue, with the advance of technology, entrepreneurs have become more independent and creative in raising capital through a process known as crowdfunding. This study intends to examine the role of Islamic crowdfunding towards SMEs sustainability in order to assist their financing need for business expansion or start-up in Malaysia. Furthermore, this study will empirically test the influence of strategic competitiveness and the mediating effect of technology adoption towards SMEs sustainability. Primary data are collected by using a simple random sampling technique from a sample of 259 SMEs in Selangor. The date was computed using SmartPLS to examine the direct and mediated effect on SME ’s sustainability. The results show that Islamic crowdfunding and strategic competitiveness positively influence SME’s sustainability. Furthermore, technology adoption significantly mediated between Islamic crowdfunding and SME’s sustainability. Thus, this study disclosed that Islamic crowdfunding will increase the capacity in boosting SMEs’ sustainability and technology adoption will mediate the relationship between Islamic crowdfunding and SME’s sustainability.